Integral sliding mode control for improved robustness and accuracy of induction motors - Mohamed, H.A.F.; Yang, S.S.; Moghavvemi, M. (2008)
This paper proposes the use of sliding mode control to improve the performance of field-oriented speed controllers of induction motors. The integral sliding mode control provides means to obtain an accurate estimate for disturbances and plant parameter perturbations. This estimator is to be used as an auxiliary control loop to reject these disturbances and parameter perturbations while avoiding chattering in the main control loop. The result is a controller with high degree of robustness and accuracy. Stability is achieved by using a design procedure based on a Lyapunov function. The feasibility of implementing such controllers is verified on a highly nonlinear system, an induction motor. Whether loaded or unloaded, the proposed integral sliding mode controller has proved to achieve high performance.